Analyzing dynamical gluon mass generation - Aguilar, Arlene C. [UNESP]; Papavassiliou, Joannis (Sociedade Brasileira Fisica, 2007)
We study the necessary conditions for obtaining infrared finite solutions from the Schwinger-Dyson equation governing the dynamics of the gluon propagator. The equation in question is set up in the Feynman gauge of the background field method, thus capturing a number of desirable features. Most notably, and in contradistinction to the standard formulation, the gluon self-energy is transverse order-by-order in the dressed loop expansion, and separately for gluonic and ghost contributions. Various subtle field-theoretic issues, such as renormalization group invariance and regularization of quadratic divergences, are briefly addressed. The infrared and ultraviolet properties of the obtained solutions are examined in detail, and the allowed range for the effective gluon mass is presented.
Keywords: Background field method; Gluon propagator; Pinch technique; Running coupling; Schwinger-Dyson equations